2012
DOI: 10.1161/hypertensionaha.111.176727
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain and Insulin Induce Sodium Pump Endocytosis in Renal Epithelium

Abstract: Cardiotonic steroids signaling through the basolateral sodium pump (Na/KATPase) have been shown to alter renal salt handling in intact animals. As the relationship between renal salt handling and blood pressure is a key determinant of hypertension, and patients with insulin resistance are frequently hypertensive, we chose to examine whether there might be competition for resources necessary for receptor mediated endocytosis. In LLC-PK1 cells, the Na/K-ATPase-α1 and carcinoembryonic antigen cell adhesion molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…The knockdown of ␣1 in the work by Xie et al was correlated with an increase in basal Src activity and activation of consequent signal transduction pathways. Although our present work does not address this issue directly, our previously published study (4) showed no relationship between Src/phosphoinositide-3-kinase signaling pathways to ouabain-induced inhibition and subsequent internalization of Na ϩ -K ϩ -ATPase in our cellular system, as opposed to results described previously by Xie et al (11,(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 98%
“…The knockdown of ␣1 in the work by Xie et al was correlated with an increase in basal Src activity and activation of consequent signal transduction pathways. Although our present work does not address this issue directly, our previously published study (4) showed no relationship between Src/phosphoinositide-3-kinase signaling pathways to ouabain-induced inhibition and subsequent internalization of Na ϩ -K ϩ -ATPase in our cellular system, as opposed to results described previously by Xie et al (11,(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 98%
“…CoV and VSV replication was not affected, as revealed by the addition of the CTSs after inoculation. Inhibition of MHV was found to be independent of the particular virus receptor being used by the virus, despite the reported interaction between CEACAM1 and ATP1A1 (41). This is in line with FIPV and MERS-CoV being similarly inhibited although they use entirely different entry receptors (54,55).…”
Section: Discussionmentioning
confidence: 54%
“…CEACAM1 has been reported to interact with ATP1A1 in porcine cells (41). Since murine CEACAM1a, the natural receptor of MHV, is a homologue thereof, we investigated whether the positive effect of ATP1A1 on MHV infection is somehow linked to MHV binding to CEACAM1a.…”
Section: Rnai-mediated Gene Silencing Of Atp1a1 Inhibits Infection Wimentioning
confidence: 99%
“…In the same way, in a culture complex model, insulin exposition raised renal NKA activity in the first 30 minutes, but it returned to the baseline levels after 2 hours and was even lower at 48-hour measurements [166]. This reduction was likewise observed after one hour of insulin exposition in another study [167]. Taken together, these results suggest a dual temporal insulin action on NKA activity.…”
Section: Glucose Effects On Renal Glucosementioning
confidence: 52%